2009
DOI: 10.1002/dvdy.21877
|View full text |Cite
|
Sign up to set email alerts
|

Recapitulation of zebrafish sncga expression pattern and labeling the habenular complex in transgenic zebrafish using green fluorescent protein reporter gene

Abstract: Human synuclein family consists of ␣-, ␤-, and ␥-synucleins. Here, we cloned three genes, sncb, sncga and sncgb from zebrafish. They encode ␤-, ␥1-, and ␥2-synucleins, respectively. The zSyn-␤, zSyn-␥1, and zSyn-␥2 proteins display 69%, 47%, and 50% identity to human ␤-synuclein and ␥-synuclein, respectively. By reverse transcriptase-polymerase chain reaction, we demonstrated that sncb and sncga mRNA were abundant in brain and eye, while sncgb expression was moderate in brain, kidney, ovary and testis. The 1.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 41 publications
1
30
0
Order By: Relevance
“…Zebrafish Synucleins-Identification of zebrafish synucleins was recently reported by two other groups (42,43). We independently cloned the same genes at the start of this study (not shown).…”
Section: Resultsmentioning
confidence: 64%
“…Zebrafish Synucleins-Identification of zebrafish synucleins was recently reported by two other groups (42,43). We independently cloned the same genes at the start of this study (not shown).…”
Section: Resultsmentioning
confidence: 64%
“…Three isoforms of synuclein (β, γ1, and γ2) have previously been partially characterized in ZF, but none appears to be the exact orthologue to human α-syn (Milanese et al 2012; Sun and Gitler 2008). ZF γ1 has been previously demonstrated to be expressed widely throughout the developing ZF brain (Chen et al 2009). Because ZF γ1 synuclein contains N-terminal repeats and hydrophobic regions similar to those of α-syn, and because expression of human α-syn rescues behavioral defects of γ1-deficient ZF embryos (Milanese et al 2012), we investigated the propensity of ZF γ1 to aggregate and induce toxicity in vitro and in vivo .…”
Section: Resultsmentioning
confidence: 99%
“…Zebrafish is a useful organism for generating transgenic animals that drive expression of tissue/cell-specific reporters, altered gene products, toxic proteins, and regulatory RNAs. Using different transgenesis approaches (Jessen et al, 1998;Kawakami, 2005;Balciunas et al, 2006;Kawakami, 2007;Yang et al, 2009) many transgenic lines have been generated to drive expression of reporters under specific promoters or enhancer elements in diverse regions of the animal, including the brain (Asaoka et al, 2002;Picker et al, 2002;Dorsky et al, 2002;Nakada et al, 2004;Gao et al, 2005;Bernardos and Raymond, 2006;Jin et al, 2006;Zhao et al, 2006;Kotani et al, 2006;Bai et al, 2007;Yeo et al, 2007;Park et al, 2007;Scott et al, 2007;Kleinjan et al, 2008;Asakawa et al, 2008;Chen et al, 2009;Kaslin et al, 2009;Scott and Baier, 2009). Furthermore, these constructs can be easily modified to allow promoter-specific cell ablations in transgenic animals.…”
Section: Regeneration In the Adult Brain Injury Methods To Induce Regmentioning
confidence: 98%